Self-efficacy and self-care behaviours among adults with antihypertensive medication adherence - Jenny Firda Len; Syarifah Nurul Yanti Rizki Syahab Assegaf; Ridha Ulfah (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Hypertension is a chronic medical condition characterized by persistently elevated systolic and diastolic blood pressure beyond normal thresholds, often termed a “silent killer.” Increased self-efficacy and effective self-care management have been shown to positively influence adherence to antihypertensive treatment. However, limited research has examined the relationship between intrinsic factors and medication adherence among patients within the Saigon Community Health Center. Purpose: To determine the relationship between self-efficacy, self-care management, and medication adherence among individuals with hypertension. Method: This research employed an analytical observational design with a cross-sectional approach. A total of 100 hypertensive patients participated, assessed using the Morisky Medication Adherence Scale (MMAS-8), the Modified General Perceived Self-Efficacy Scale, and the Hypertension Self-Management Behavior Questionnaire (HSMBQ). Univariate analysis was used to describe respondents’ demographic characteristics, while bivariate analysis was performed using Spearman’s correlation test. Results: The findings showed that 87% of respondents demonstrated good self-care management, 85% had high self-efficacy, and 51% adhered to their prescribed medications. Spearman’s correlation analysis revealed a significant relationship between self-care management and medication adherence (p = 0.002, r = 0.311), as well as between self-efficacy and adherence (p = 0.009, r = 0.262). Conclusion: Both self-efficacy and self-care management were found to have a significant but weak positive correlation with medication adherence. Strengthening patients’ motivation and promoting consistent engagement in hypertension management are essential to reducing related complications.